Geographic Stomatitis with Multiple Areas Involvement of Oral Cavity: A Case Report and Review of Literatures - Abbasi, Farid; Sehatpour, Aliyeh; Sajedi, Seyed Masoud; Bahadori, Parisa; Nouri, Mohadeseh (Galen Medical Journal, 2021)
Background: Geographic stomatitis is an uncommon migratory benign lesion of oral mucosa with unknown etiology. It can affect all the areas of the oral mucosa, but the dorsum and lateral borders of the tongue are the most commonly involved areas called geographic tongue. The clinical appearance of this condition is the oval or circular erythematous areas with irregular elevated keratotic borders. These characteristic features of geographic stomatitis are diagnostic for all clinicians when appearing on the dorsum of the tongue, despite other affected areas of oral mucosa that can confuse clinicians. This condition may be associated with some diseases such as psoriasis, Reiter’s syndrome, and atopic conditions, so the clinicians should rule out these diseases and diagnose the geographic stomatitis. Case Report: A 17-year-old male attended to our department for a routine dentistry checkup. During the intraoral examination, we found multiple erythematous areas surrounded by a thin white border on different surfaces of his oral cavity. His extraoral examinations were completely normal. Conclusion: Due to the rarity of this lesion on the other sites of oral mucosa rather than dorsum and lateral borders of the tongue such as labial mucosa, buccal mucosa, the floor of the mouth, ventral surface of the tongue, and palate, it is necessary to report, study and evaluate each case of this condition that clinicopathologic findings have confirmed this diagnosis, to treat and advice these patients on the best approach. [GMJ.2021;10:e2071]